Nacionalismo Vs Globalización - Pereznieto Castro, Leonel (UNIVERSIDAD DE SONORA, 2017)
In the document the author refers to the Nationalism and to the Globalization, two concepts which origin, nature and development are different, they are opposed and in many senses there have become antagonistic concepts. The Nationalism of State, it is today a hollow and rhetorical phrase that there keep on using groups that find in it the echo of its orphanage. The Globalization, where we are now, has opened the country to the world and nowadays we have an international scrutiny ....and constitutes an important pressure for the necessary changes to the country, but especially, for the first time in the national life, with the well canalized economic growth and the participation of the civil society organizations, if the economic policies are hit, the horizon where it can go over, it is to shorten the abyss that we have nowadays between social classes and the poverty of the country. In short, the Nationalism is an ideology, the Globalization is a process.